IMAGE AS A TOOL OF DEVELOPMENT OF A SOCIAL PARTNERSHIP SYSTEM AND A SUPPLYING COMPETITIVENESS OF THE UNIVERSITY - Konstantin V. Kovtsev (Статистика и экономика, 2016)
The article presents the main components of the university’s image as a tool of social partnership development. It focuses on the issues of forming a positive image of the university. The most preferable approaches to image formation are identified. It is proposed to consider the system of social partnership as a specific translator for opinions about the institution that transfers from partners and individuals, who are accepted for internal affairs of the university’s activities due to partner structures on a general public and consumer audience of high school. The author offers to improve the image of university developed of social partnership. The university’s activities for development of its brand which can be implemented by using the approaches described in the paper are considered. The article contains developed image-building mechanisms which make it possible to get bonuses for participation in the partnership structure by partners and which promote the competitiveness of the university.